Manfaat Kegiatan Kepramukaan Dalam Melatih Kerjasama Siswa Pada SMA Negeri 3 Buru - Siti Nadifa; Aisa Abas; Fatima Sialana (Jayapangus Press, 2023)
Cooperation is one of the characteristics that must be possessed by every individual because humans are social creatures who need other people. However, what happened to the students of SMA Negeri 3 Buru, the collaborative personality seemed to fade in students, especially thanks to technological advances that gave students the feeling that they could solve problems, solve problems on their own in addition to developing children's character through extracurricular activities that students can participate in at school. outside of teaching and learning activities. This study aims to determine the benefits of scouting activities to train student collaboration at SMA Negeri 3 Buru. This research was conducted at the gudep Sawaka Bakti, the base of SMA Negeri 3 Buru, the Waeapo branch of the Buru branch. Retrieval of research information through observation expositions, interviews and also documentation. This study involved several selected sources related to the research title. This study uses a qualitative descriptive method that uses observation guidelines, interview guidelines, and documentation guidelines. The results of this study indicate that cooperation is an important thing that must be developed in students, and scouting activities can be a solution to train students' cooperation, can develop delicate abilities in students and develop the character of the nation's children through activities in scout extracurricular activities.